Increased incidence of metachronous gastric neoplasm after endoscopic resection in patients with synchronous gastric neoplasm - Ga-Yeong Shin; Hye Jin Cho; Jae Myung Park; Chul-Hyun Lim; Yu Kyung Cho; Myung-Gyu Choi (BMC Gastroenterology, 2020)
Abstract Background Recurrence risk is a major concern after endoscopic resection (ER) of gastric neoplasms. This study was to compare metachronous risk in patients with and without synchronous neoplasms after complete ER. Methods After ER for gastric neoplasms, patients were divided into those with and without synchronous neoplasm. The metachronous risk of gastric neoplasms was compared between the two groups. Results After ER of 678 cancers and 891 adenomas, synchronous neoplasm was found in 11.8% of cancers and 11.4% of adenomas. In the multiple (n = 182) and the single group (n = 1387), metachronous neoplasms occurred in 18.1 and 8.6%, respectively (HR 2.40; 95% CI, 1.62–3.34). When the pathology of the recurred lesion was limited to cancer, metachronous risk was also significantly higher in the multiple than in the single group (HR, 2.2; 95% CI, 1.17–3.85). In the recurred pathology of the multiple group, cancer development was frequently observed in patients with cancer compared to those with only adenomas in the synchronous lesion (67.0% vs. 13.0%, respectively; P = 0.023). Conclusions This study demonstrated that metachronous risk was significantly higher in patients with synchronous gastric neoplasms after ER. Therefore, meticulous examination is important in patients with synchronous neoplasm.